The Grammatical Errors in the Translational Text: Indonesian-English Structure - Aini, Nurul (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2018)
This paper discussed the study of English and Indonesian word construction based on grammatical errors. Grammatical errors were analyzed by error analysis. The purpose of this paper wanted to know the kinds of grammatical errors and the factors caused it. The qualitative approach was used in this research as the methodology because this study described the data without analysis statistic. The qualitative descriptive revealed the phenomena of linguistic which found in the translation text. In data collection, the researcher used text translation, Indonesian-English that had translated by the fourth semester of student’s English Department. Moreover, the researcher read deeply and grouped and noted the data to find the valid data. The result of this paper were 11 kinds of grammatical errors, they are: misuse of determiner, omission of determiner, misuse of verb, misuse of auxiliary verb, omission of verb, misuse of preposition, misuse of conjunction, misuse of pronoun, omission of pronoun, misuse of singular noun, and misuse of Noun Phrase (NP). In addition to, this study found the factors of the grammatical errors, they are; first, interference of the first language, namely Indonesian. Second, the difference between Indonesian and English structure was also the factor of the grammatical errors.